(NrAS^ET TERMODINAMI^ESKIH SWOJSTW GAZOW I VIDKOSTEJ METODOM IDEALXNYH KRIWYH (B/s - (NnEDOSTUP(B, (NwADIM iWANOWI^s; (NgALXKEWI^(B, (NeWGENIJ pETROWI^s ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 186-194 (250 (NNAZW(B.)s
Keywords: (NgAZYs -- (NtERMODINAMI^ESKIE SWOJSTWAs -- (NrAS^ETs; (NvIDKOSTIs -- (NtERMODINAMI^ESKIE SWOJSTWAs -- (NrAS^ETs